THE PHYSICAL PHENOMENON OF THE «MÖSSBAUER EFFECT» - Shokanov А.К.; Evniev Б.Е.; Ospanbekov Е.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In this article, the relevance is the physical phenomenon of the "Mössbauer effect", its application and practical significance for science. The article deals with resonant absorptions of gamma radiation, the history of the discovery of this effect and the experiments conducted by the scientist. The concepts of the decay of the nucleus, the energy of the excited state, and the measurement of energy using this effect are considered. The Mossbauer Effect is an example of a physical phenomenon that has found application in many fields of science: chemistry, nuclear physics, solid-state physics, etc. This work is intended to explain the essence of the Mössbauer effect and to show that the discovery of this effect was of great fundamental and practical importance for science as a whole.